Detection of the viable myocardium. A perfusion scintigraphic study, before and after coronary bypass surgery in myocardial infarction patients - Chalela,Willliam A. (1999)
OBJECTIVE: To compare single-photon-emission computed tomography (SPECT) imaging scans using 201Tl and 99mTc-MIBI in detection of viable myocardium, in regions compromised by infarction. METHODS: Thirty-two (59.3±9.8 years old and 87% male) myocardial infarction patients were studied. All had Q waves on the ECG and left ventricle ejection fraction of <50%. They underwent coronary and left ventricle angiographies and SPECT before (including 201Tl reinjection) and after coronary artery bypass surgery (CABG). Improvement in perfusion observed after surgery was considered the gold standard for myocardial viability. RESULTS: Among 102 studied regions of the heart, there were 40 (39.2%) areas of transient perfusion defects in the conventional protocol with 201Tl and 52 (51.0%) after reinjection. Therefore, 12/62 (19.4%) more viable regions were identified by reinjection. Using 99mTc-MIBI, only 14 (13.7%) regions with transient defects were identified, all of which were seen also in 201Tl protocols. After surgery, 49 of a total of 93 regions analyzed (52.7%) were viable. Sensitivity, specificity, accuracy, positive and negative prediction values were, respectively, 201Tl SPECT scans - 65.3%, 90.9%, 77.4%, 88.9% and 70.2%, reinjection protocol with 201Tl scans - 81.6%, 81.8%, 81.7%, 83.3% and 80.0%; 99mTc-MIBI SPECT scans - 20.4%, 90.9%, 53.8%, 71.4% and 50.6%. Logistic regression demonstrated that the reinjection protocol with 201Tl was the best predictor of viability (P<0.001). CONCLUSION: Our data suggest the election of 201Tl for viability studies, especially when using the reinjection protocol.